Kajian Efisiensi Energi Sebagai Implikasi Penerapan Konsep Tri Hita Karana di Movenpick Resort & Spa Jimbaran Bali - Andy Nudyanto; Ida Ayu Kalpikawati; Ni Kade Juli Rastitiati; Ni Wayan Chintia Pinaria (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2022)
This study discusses energy efficiency at the Movenpick Resort & Spa Jimbaran Bali as an implication of the application of the Tri Hita Karana concept. The purpose of this study is to examine the amount of energy efficiency as an implication of implementing THK at Movenpick Resort & Spa Jimbaran Bali. The energy constraints studied include water and electricity. The time period studied is 12 months, consisting of 6 months before the implementation of the THK, namely january-june 2018 and 6 months after the implementation of the thk in july-december 2018. The data analysis technique uses paired sample t-test. The results of the paired sample t test for water efficiency with a significance value of 0.029 while for electricity efficiency a significance value of 0.870, there was no difference in energy efficiency from the implications of implementing Tri Hita Karana at Movenpick Resort & Spa Jimbaran Bali so that further planning efforts are needed to improve water and electricity efficiency at Movenpick Resort & Spa Jimbaran Bali.